The Effect of Pornography on Social Media on Sexual Harassment Behavior among Adolescents in Yogyakarta - Mega Ardina (Program Studi Ilmu Komunikasi FISIP UM Buton, 2021)
Social media has been utilized by a number of thoughtless people to share pornographic information or content that may influence sexual harassment behavior. This study analyzes various kinds of pornographic scenes that are frequently accessed by teenagers in social media platforms and the influencing factors of those pornographic scenes on behaviors considered sexual harassment among teenagers in Yogyakarta. This study was done by using quantitative method and descriptive approach with questionaires responded by 60 teenagers in Yogyakarta chosen by random as the data-collecting technique. The data was, then, analyzed quantitatively by using software SPSS 24.0. The result shows that the kinds of pornographic scenes frequently watched by teenagers in Yogyakarta are pictures and videos. The factors that influence sexual harassment among teenagers are motive, need, psycho-social, and stimuli. Out of the four influencing factors, motive brings the highest influence towards sexual harassment behavior among teenagers.